Cover Image. Issue 5 (30th April 2020) - Brusch, George A.; Mills, Anthony M.; Walman, Rachel M.; Masuda, Garrett; Byeon, Andy; DeNardo, Dale F.; Stahlschmidt, Zachary R.
Abstract : ON THE COVER : The cover image is based on the Research Paper Dehydration enhances cellular and humoral immunity in a mesic snake community by George A. Brusch IV et al., https://doi.org/10.1002/jez.2358 . Photo Credit: Anthony M. Mills.